Techno-Economic Optimization of a Grid-Tied Hybrid PV–Battery System under Vietnam Climatic Conditions - Vu Trong Tuan; Cao Hoang Kha; Nguyen Van Minh (European Scientific Journal, ESJ, 2026)
The rapid growth of electricity demand in Vietnam has increased pressure on the national power grid and highlighted the need for efficient renewable energy utilization. This study investigates the techno-economic performance of grid-connected photovoltaic–battery (PV–BESS) systems under Vietnam’s climatic conditions and electricity tariff structure. A detailed simulation framework is developed incorporating PV generation, battery storage dynamics, inverter efficiency, and grid interaction. An energy management system (EMS) is implemented to coordinate power flows and evaluate three configurations: PV-only, PV+BESS, and PV+BESS with time-of-use (TOU)–based operation. Simulation results show that integrating battery storage significantly improves renewable energy utilization, increasing the self-consumption ratio (SCR) from 0.36 to 0.62 and the self-sufficiency ratio (SSR) from 0.40 to 0.68. The TOU-based strategy further enhances operational flexibility by enabling peak shaving and tariff-aware energy shifting. As a result, grid import is substantially reduced while maintaining battery operation within safe SOC limits. The results demonstrate that hybrid PV–battery systems with tariff-aware energy management provide a technically viable and economically attractive solution for improving renewable energy utilization in Vietnam and similar tropical regions.